Filtered Social Learning - Niehaus, Paul (Journal of Political Economy, 2011)
Knowledge sharing is economically important but also typically incomplete: we “filter” our communication. This paper analyzes the consequences of filtering. In the model, homogeneous agents share knowledge with their peers whenever the private benefits exceed communication costs. The welfare implications of this transmission mechanism hinge on whether units of knowledge complement, substitute for, or are independent of each other. Both substitutability and complementarity generate externalities; cheaper communication eliminates externalities in the former case but not necessarily in the latter. Complementary basic skills such as numeracy catalyze technology adoption, and adoption may be path dependent even when payoffs are certain and independent across agents.